Human rights law in the development of hydropower projects in transboundary context - Tignino, Mara; Jara, Diego (Frontiers in Climate, 2024)
Human rights obligations are owed by states to the individuals in their territory and under their jurisdiction and may also arise in extraterritorial contexts. This document provides an overview of how various human rights and in particular the human right to safe drinking water and indigenous peoples' rights are related to hydropower development. This analysis, will present available international law tools and mechanisms including river basin organizations and judicial bodies which may conciliate tensions between and within states when the development of hydropower project risk to affect the quantity or the quality of water provided to local and vulnerable communities.